Character Values in Gymnastics Activities at Jatisari 1 SDN - Fitrian Prila Wardani; Alfi Mukhlis Kurniawan (International Journal of Science and Applied Science: Conference Series, 2022)
Character values are an important part of education in elementary schools. One way to develop character values in children is through sports activities, especially gymnastics. Gymnastics is a sporting activity that requires cooperation, self-confidence, perseverance, discipline, and other positive values (Rachmadayanti, 2017., Annsia 2019., & Wuryandani, 2014). This study aims to examine the character values that are developed through gymnastic activities at SDN Jatisari 1. Through this research, it is hoped that it can provide an overview of the character values that are developed in children through gymnastic sports activities. This research also aims to contribute to the development of learning programs in elementary schools, especially in developing character values in children through sports activities. In this study, the method used was direct observation and interviews with sports teachers and students involved in gymnastic sports activities. The data obtained will be analyzed qualitatively and interpreted in the form of findings that can describe the character values developed in gymnastics activities at SDN Jatisari 1.